2008
DOI: 10.1161/circulationaha.107.188525
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous and Minimally Invasive Valve Procedures

Abstract: Abstract-The incidence of valvular heart disease is expected to increase over the next several decades as a large proportion of the US demographic advances into the later decades of life. At the same time, the next several years can be anticipated to bring a broad transition of surgical therapy to minimally invasive (minithoracotomy and small port) access and the more gradual introduction of percutaneous approaches for the correction of valvular heart disease. Broad acceptance of these technologies will requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(40 citation statements)
references
References 91 publications
(83 reference statements)
0
37
0
3
Order By: Relevance
“…Nesse grupo, a abordagem por cateter tem elevada chance de sucesso e pode oferecer mortalidade inferior àquela esperada com o tratamento cirúrgico. 7,[10][11][12]15 O risco cirúrgico pode ser estimado por diversos escores. Os mais empregados são o EuroSCORE 16 e o STS 17 , validados em centros europeus e americanos, respectivamente.…”
Section: Seleção De Pacientesunclassified
“…Nesse grupo, a abordagem por cateter tem elevada chance de sucesso e pode oferecer mortalidade inferior àquela esperada com o tratamento cirúrgico. 7,[10][11][12]15 O risco cirúrgico pode ser estimado por diversos escores. Os mais empregados são o EuroSCORE 16 e o STS 17 , validados em centros europeus e americanos, respectivamente.…”
Section: Seleção De Pacientesunclassified
“…At this point in time, it is important for professional societies to critically review the available TAVI techniques and their results, as well as propose recommendations for their use, development in clinical practice, and further research. 9,10 On the 18 -19th of November 2007, a committee of experts, including EACTS and ESC representatives, met. The consensus reached is summarized in the current document, which was approved first by the committee members and subsequently by the board of both professional societies involved.…”
Section: Preamblementioning
confidence: 99%
“…Although these procedures can be performed in cardiac catheterization suites, a recent expert panel suggested that they are best performed in a hybrid operating theatre with fixed fluoroscopic imaging. 9 A hybrid operating theatre ensures sterility and the ability to rapidly convert to a conventional surgical approach during unforeseen complications, while maintaining the fluoroscopic capabilities of a catheterization laboratory.…”
Section: Techniques Used In Valve Implantationmentioning
confidence: 99%